The Oxford Book of English Verse, 1250-1900 - Quiller-Couch, Arthur, 1863-1944 (Salt Lake City, UT : Project Gutenberg, 2021)
"The Oxford Book of English Verse, 1250-1900" by Arthur Quiller-Couch is an anthology published in 1900. This influential collection shaped popular taste in poetry for generations across the British Empire. Designed to surpass Palgrave's famous "Golden Treasury," it focused on lyric poetry and included twice as many works. Carried as a knapsack book through war and peace, it sold over 500,000 copies and inspired an entire series of Oxford poetry anthologies spanning multiple languages and traditions. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Oxford_Book_of_English_Verse
Release date is 2021-10-27
Chuck Greif and the Online Distributed Proofreading Team at http://www.pgdp.net (This file was produced from images available at The Internet Archive)
Keywords: English poetry